The predictive value of Golgi protein 73 in differentiating benign from malignant liver tumors. - Mirelle E E Bröker; Jan N M Ijzermans; Caroline D M Witjes; Hanneke J van Vuuren; Robert A de Man (PLoS ONE, 2014)
In the work up of primary solid liver lesions it is essential to differentiate correctly between benign and malignant tumors, such as hepatocellular adenoma (HCA) and hepatocellular carcinoma (HCC) respectively. A promising new marker to detect HCC is Golgi Protein 73 (GP73). Studies comparing patients with HCC and cirrhosis with normal controls suggested that GP73 is specific for patients with HCC; however, patients with other liver tumors were not included. We therefore studied the predictive value of GP73 in differentiating between solid benign and malignant liver tumors.This study included 264 patients: 88 patients with HCC, 88 with hepatocellular adenoma (HCA), and 88 with focal nodal hyperplasia (FNH). A blood sample was collected from each patient to measure GP73 levels using a quantitative ELISA assay and differences in outcome between subgroups were compared. The receiver operating characteristic (ROC) curve, sensitivity and specificity of GP73 were calculated and compared to alpha-fetoprotein (AFP) levels.When comparing malignant and benign liver tumors the area under ROC was 0.701 and 0.912 for GP73 and AFP respectively. Test characteristics revealed a sensitivity of 60% for GP73 and 65% for AFP; in addition the specificity was 77% for GP73 and 96% for AFP.Although the literature suggests that GP73 is a valuable serum marker in patients with HCC, the serum concentration may also be increased in patients with solid benign liver tumors. Therefore, a GP73 assay is less suitable for discriminating between primary malignant and benign tumors of the liver.